Problems and Solutions of Money Politics During Elections from an Islamic Perspective - Ahmat Suaidy; Babun Suharto; Retna Anggita Ningsih (Eastasouth Institute, 2026)
Elections in Indonesia are often associated with the practice of giving money to the public. Giving money to the public has two different perspectives. First, whether it is permissible, and second, whether it is not. This study aims to further examine the prohibitions and permissibility of this practice. The research method used is a qualitative literature study, with data sources consisting of previous research, journals, and articles related to our discussion. The results of our study are: first, the problematic issue during elections is that giving money during elections is commonplace and is considered a form of bribery, which is forbidden in Islam. Second, giving money to the public by prospective leaders is permitted on the condition that the gifts are in the form of gifts, grants, and alms. However, the public may not buy food or drinks from the money, but rather allocate it for public purposes, such as road renovations and mosque construction.